(untitled) (Research, Society and Development, 2022)
Objective: To analyze the association between sleep quality indicators and eating habits in adolescents. Material and Methods: This is a cross-sectional study conducted with adolescents (age 10-19 years) followed up at the Adolescent Outpatient Clinic. Anthropometric and body composition parameters, sleep quality indicators, and eating behavior were evaluated. Body composition was measured using electrical bioimpedance. Sleep quality was assessed by the Pittsburg Sleep Quality Index (PSQI), excessive daytime sleepiness by the Epworth Sleepiness Scale (ESS), eating behavior was assessed by the Brazilian Food Frequency Questionnaire (FFQ). Linear regression analyses were used to verify the association between outcome and independent variables. Results: Thirty-five adolescents (mean age 12.9 ± 2.0 years old) were evaluated. There was a significant association between BMI and daytime sleepiness (p=0.010), fat mass (%), and sleep quality (p=0.046) while drinking at least 5 glasses of water was associated with sleep efficiency (p=0.029). Adjusted linear regression showed that BMI (β= -0.364; p=0.001) and age (β= -0.30; p<0.001) were negatively associated with hours of sleep, whereas blood pressure (β= 0.196; p<0.001) and the frequency of consumption of the group of cereals, tubers, and pasta (β=1.451; p<0.001) were positively associated. Conclusion: Adolescents with a higher % fat mass and BMI showed worse sleep quality and daytime sleepiness. Drinking at least five glasses of water can improve sleep efficiency. The consumption of cereals, tubers, and pasta, can contribute to longer sleep duration.